Direct Coagulation Casting of Alumina Suspension from Calcium Citrate Assisted by pH Shift. Issue 4 (4th February 2014) - Xu, Jie; Zhang, Yanxue; Qu, Yanan; Qi, Fei; Zhang, Xiaoyan; Yang, Jinlong; Gauckler, L.
<x xml:space="preserve">Abstract</x> Direct coagulation casting of alumina suspension via controlled release of high valence counter ions (DCC–HVCI) using calcium citrate as coagulating agent was reported. Hydrolysis of glycerol diacetate shifts the pH of suspension to weakly acidic region which helps to decompose calcium citrate and release calcium ions. The effect of concentration of glycerol diacetate and calcium citrate on the pH and viscosity of alumina suspension was investigated at 25°C and 60°C, respectively. The pH of suspensions with glycerol diacetate and calcium citrate decreases to 8.6 and 7.5 treated at 25°C and 60°C, respectively. It is indicated that high viscosity is achieved by adding 2 vol% glycerol diacetate and 0.5 wt% calcium citrate which is enough to coagulate the suspension. Green body with compressive strength of 1.0 MPa is obtained by treating the alumina suspension with 2 vol% glycerol diacetate and 0.5 wt% calcium citrate at 60°C for 1 h. The alumina ceramics sintered at 1550°C have homogeneous microstructure with relative density above 99.0%.